The influence of regional revenue and expenditure budget and the quality of financial reporting on corruption cases in regional government - Doa Mardikhayani P; Lisa Kartikasari Z (Proceeding International Conference on Accounting and Finance, 2025)
To overcome the negative impacts of corruption, many countries implement fiscal decentralization and regional autonomy, including Indonesia. Through fiscal decentralization, local governments are given the right to collect local own-source revenue and determine the budget value and the obligation to prepare financial reports. This study aims to test the effectiveness of the implementation of fiscal decentralization in overcoming the problem of corruption by testing these three aspects. The sample of this study consisted of 34 provincial governments in Indonesia with a period of 2018-2022 for the independent variable and 2019-2023 for the dependent variable. The test was carried out using binary logistic regression data analysis techniques using SPSS. The results of the hypothesis test show that local own-source revenue has a positive effect on corruption cases, capital expenditure does not affect corruption cases, and the financial reporting quality has a negative effect on corruption cases. This study concludes that local governments with large local own-source have a high risk of corruption cases. To overcome this, it is necessary to implement adequate internal control and risk-based internal audit as well as a commitment to present quality financial reports.